Factor analysis of indicators of physical and functional preparation of basketball players - Tyshchenko, V.; Hnatchuk, Y.; Pasicnyk, V.; Bubela, O.-O.; Semeryak, Z. (Journal of Physical Education and Sport, 2018)
The problem of physiological study of non-traditional means of training attracts a lot of scientists` attention in recent years. This is due to the need to provide a maximum development of certain muscle groups and direction of the training process. Proper use of simulators weight machines bring positive results. Obviously, an important step in the use of technology is the right choice for team sports coaches and personal trainers for the effectiveness of the training process. One effective component of this process is the inclusion to a training program with the help of physical exercises would be TRX® function loops. Among specialists of functional and physical training innovation as TRX® - training is one of the best equipment for complex solution of the tasks. This exercise is an exercise using body weight. It was designed to develop strength, power, core stability, flexibility and balance. TRX® is the valuable creation for the sports industry of any levels. TRX® Training - Suspension Training became commonly usable for Fitness Health Clubs, Professional Sports and Elite Strength Conditioning Workout for Sports Teams. Therefore, it was suggested the use of TRX® exercises in preparation of basketball players. The results of the study clearly demonstrated that the inclusion in the training program for basketball players training with functional loops TRX® contributed to a significant increase in the level of their overall physical performance and aerobic capacity of the organism. Utilization of TRX® in the training process can be considered as an important factor in increasing the efficiency of preparation in basketball.